Exploring the impact of meditation therapy on CD4 levels in HIV/AIDS patients at Karawang hospital - Dea, Dea; Karo, Marni Br; Wati, Puri Kresna (PT. Mega Science Indonesia, 2024)
The HIV/AIDS epidemic remains a significant global health concern, with increasing prevalence in Indonesia's Karawang Regency. People living with HIV/AIDS face numerous challenges, including a decline in immune function and CD4 T-cell depletion. While antiretroviral therapy (ART) is the primary treatment, there is a growing interest in complementary therapies to support immune function and overall well-being. This study aimed to investigate the effect of meditation therapy on CD4 levels in HIV/AIDS patients at Karawang Regional General Hospital. A quasiexperimental study with a prepost design was conducted on 15 HIV/AIDS patients with CD4 levels ranging from 200–500 cells/mm3. The participants engaged in meditation sessions twice a week, twice daily, for one month. CD4 levels were measured before and after the intervention. Demographic data were collected, and statistical analyses were performed via paired t tests (p<0.05). Most of the participants were male (80%), aged 31-37 years (46.7%), and had a vocational high school education (40%). Preintervention CD4 levels ranged from 226 to 459 cells/mm3 (mean: 334.87±57.583), whereas postintervention levels ranged from 220 to 467 cells/mm3 (mean: 340.93±62.721). A paired t test revealed no statistically significant effect of meditation therapy on CD4 levels (p=0.150). This study revealed no significant increase in CD4 levels following a one-month meditation intervention in HIV/AIDS patients. While this research does not support the use of short-term meditation therapy to increase CD4 levels in HIV/AIDS patients, it underscores the need for further investigation of complementary therapies for this population.